Visitor diversification in pilgrimage destinations: comparing national and international visitors through means-end. Issue 4 (1st July 2021) - Progano, Ricardo Nicolas; Kato, Kumi; Cheer, Joseph M.
Abstract: In contemporary society, spirituality has dissociated from the tenets of organized 'official' religion, resulting in a rise of 'private' spirituality, defined by each individual's beliefs. In this context, visitors from a great variety of national backgrounds are increasingly visiting pilgrimage sites across the globe, even if they have little to no cultural connections to them, bringing with them a diverse range of values to the pilgrimage site. Despite the growing presence of international visitors from across the globe, nationality has not been a studied factor when researching tourism in pilgrimage-related destinations. In order to bridge this research gap, the present study's objective is to examine visitor diversification in pilgrimage tourism through a study of similarities and differences of values among domestic and international visitors. Utilizing means-end as a qualitative research methodology, the two most numerous nationalities were sampled: Japanese and Australians. Fieldwork was conducted in the Nakahechi trail of Kumano Kodo, an ancient pilgrimage site located in Tanabe city (Japan) developed for international tourism. The Nakahechi route is a popular route for both domestic and international visitors due to its cultural significance, easy access and moderate challenge. Results showed a variety of similarities and differences between the sampled nationalities, demonstrating a growing diversification in sacred sites which incorporates a complex range of elements related to leisure, sports, intercultural exchange, nostalgia, escapism and relaxation, beyond a continuum of contemporary spirituality and traditional religion. In conclusion, it was observed that nationality is a fundamental factor for studying pilgrimage tourism in contemporary society. As pilgrimage sites continue to develop into international destinations, nationality is an important factor that requires further attention from academics. Results also have practical implications for local administrations aiming to develop their pilgrimage resources to international visitors.